Altered Biodistribution on 99mTc-Dimercaptosuccinic Acid Renal Scan. (12th April 2023) - Mercer, Megan K.; Parisi, Marguerite T.; Revels, Jonathan W.; Blacklock, Lisa; Elojeimy, Saeed
Abstract: 99m Tc-dimercaptosuccinic acid ( 99m Tc-DMSA) scans are used to evaluate renal cortical defects typically related to parenchymal scarring or pyelonephritis, and ectopic renal parenchyma. 99m Tc-DMSA binds to metalloproteins in proximal tubular cells and typically localizes to the renal cortex, with minimal excretion. Planar and SPECT images are obtained 2 to 4 hours after IV administration of 99m Tc-DMSA. Altered 99m Tc-DMSA biodistribution has been reported in various conditions, including renal injury, technical issues, infiltrative processes, and hematologic disorders. Here, we present a case of altered biodistribution, with hepatic and splenic radiotracer uptake in the setting of hepatosplenomegaly and hematologic abnormalities concerning for a systemic hematologic disorder/lymphohistiocytosis.